An Ethico-Philosophical Disquisition of Homosexuality - Joseph P Opuowei; Sotonye Big Alabo; John E Umezurike (Asian Journal of Philosophy and Religion, 2023)
The practice of homosexuality in several nations has been the subject of intense controversy recently. In addition to eroding the sense of identity of individuals who practice it, homosexuality—also known as same-sex relationships or marriage—has also been condemned for undermining the order of creation and endangering the survival of many societies. This paper examines homosexuality as an act and its consequent implications for the community in which the actor belongs. The paper employs the method of critical analysis; hence, using Kantian ethics, the utilitarian view, situation ethics, sexual ethics, and Christian ethics to look at the issue of homosexuality; and also, the natural law theory of morality, which states that since what is natural is morally right and what is unnatural is morally wrong, homosexuality as an act is unnatural, hence it is morally wrong. To conclude, we are of the opinion that an unauthentic lifestyle has detrimental consequences for society in general and the individual in particular